1989
DOI: 10.1159/000238660
|View full text |Cite
|
Sign up to set email alerts
|

New Forms of Multidrug Therapy for the Treatment of Leprosy

Abstract: Since 1970, when the lifelong monotherapy with dapsone (DDS) in leprosy could be replaced by short-term combination therapy with rifampicin + isoniazid + protionamide-!-DDS (Isoprodian-RMP), chemotherapeutic research was faced with two problems: (1) to find alternative treatment regimens for cases of intolerance, and (2) to work out forms of therapy allowing a further reduction of the average treatment time of 2 years. The present paper describes the attempts made to find solutions to these problems. With two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…It may be stated as the rule of thumb [16,17] that drugs with a long t 50 may be potentially dangerous in this respect, because the parasites will be inevitably exposed to sub-MIC drug concentrations for long periods of time [17][18][19]. From this point of view, CF offers an advantage: RIF, SXT or INH are all substances with a rather short t 50 compared to chloroquine or mefloquine for example.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be stated as the rule of thumb [16,17] that drugs with a long t 50 may be potentially dangerous in this respect, because the parasites will be inevitably exposed to sub-MIC drug concentrations for long periods of time [17][18][19]. From this point of view, CF offers an advantage: RIF, SXT or INH are all substances with a rather short t 50 compared to chloroquine or mefloquine for example.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp. carriers [6]; they postulated a 'synergism' between CF components [19] and stressed the need for a fixed combination, particularly for low-income countries [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Experience and single observations are already available with all three combinations. Up to now, Co trifazid has been used to treat leprosy [15][16][17][18] including ocular leprosy, tuberculosis [18,19] salmonelloses including typhoid fever [20], opportunistic [21,22] and associated infec tions (e.g. tuberculosis in AIDS), inflamma tions in the region of the head (otitis, sinusitis, oral cavity) and tourist enteritis.…”
Section: Cotrifazid -An Agent Against Malariamentioning
confidence: 99%
“…In continuation of previous studies re sulting in the introduction of integrated complex combinations in the treatment of tuberculosis [9,17], leprosy [8,10,13] and salmonelloses [12], medications against non-tuberculosis mycobacterioses (MOT) have been worked out, with special em phasis on mycobacteria belonging to the MAIS complex (M. avium, M. intracellu läre, M. scrofulaceum). These mycobacte ria are difficult to influence with chemo therapy.…”
Section: Medications Against Mot-mycobacteriosesmentioning
confidence: 99%
“…Experience gained in the treatment of infectious diseases in third world coun tries indicates that forms of combinations in which the components of the combina tion [8,9,13] have to be taken separately, are in most cases unsuccessful in outpa tient treatment, because this asks too much of the patients. In these countries in patient treatment is generally impossible, due to the lack of hospitals.…”
Section: Fixed Combinationsmentioning
confidence: 99%